An Analysis of Contextual Meaning on Michael Bube’s Song Lyrics - Ni Wayan Suastini; Ni Nyoman Deni Ariyaningsih; Dafriana Mamun (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
Abstract This study aims explain the contextual meaning found in the lyrics of Michael Buble song lyrics used theory of Lyons (1981) and to explain the context of the situation support the analysis of meaning in the lyrics of Michael Buble song lyrics used theory of Halliday and Hasan (1985). To analyze the data the researcher used descriptive qualitative method. The result showed there are 4 contextual meaning found, these contextual meaning grouped in 2 or (50%) words , 1or (25%) phrase and 1 or (25%) clause. The e contextual meaning consist of informal language ,figurative language, which analyzed based on the context of the situation showed that the field or the topic of each song about love between young adults, Michael Buble and her story about love and her child. the tenor of the participant of each song has similarity using figurative language , idioms, informal language. The mode of each song is the same that all of them are written text but can be read if those song are sung.